2020
DOI: 10.1097/hp.0000000000001250
|View full text |Cite
|
Sign up to set email alerts
|

Response to a Skin Puncture Contaminated with 238Pu at Los Alamos National Laboratory

Abstract: The three principal pathways for intakes of plutonium are ingestion, inhalation, and contaminated wounds. In August 2018, a glovebox worker at Los Alamos National Laboratory (LANL) sustained a puncture from a thread of a braided steel cable contaminated with 238Pu. The puncture produced no pain, no blood, and little or no visible mark. As a result, the potential for a contaminated wound was not immediately recognized, and a wound count was not conducted until elevated urine bioassay results were received 12 d … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…The typical minimum detectable activities (MDAs) for a 500-s wound count, assuming surface activity (<1 mm wound depth), are 10 Bq, 5 Bq, and 3 Bq for 239/240 Pu, 238 Pu, and 241 Am, respectively. For 1 to 3 mm wound depth, the corresponding MDAs are 16 Bq, 8 Bq, and 3 Bq, respectively, for 239/240 Pu, 238 Pu, and 241 Am (Klumpp et al 2020).…”
Section: Review Of Lanl Casesmentioning
confidence: 99%
“…The typical minimum detectable activities (MDAs) for a 500-s wound count, assuming surface activity (<1 mm wound depth), are 10 Bq, 5 Bq, and 3 Bq for 239/240 Pu, 238 Pu, and 241 Am, respectively. For 1 to 3 mm wound depth, the corresponding MDAs are 16 Bq, 8 Bq, and 3 Bq, respectively, for 239/240 Pu, 238 Pu, and 241 Am (Klumpp et al 2020).…”
Section: Review Of Lanl Casesmentioning
confidence: 99%
“…With regard to wound contamination, excision of the wound site is often practiced and has indeed been employed in several cases of accidental contamination in man (Bailey et al, 2003;Laroche et al, 2010;Schadilov et al, 2010;Sugarman et al, 2018;Klumpp et al, 2020). In general surgical removal of the contaminated site is combined with both local (washing of the wound) and intravenous DTPA.…”
Section: Data Availability Statementmentioning
confidence: 99%
“…Cases of actinide contamination by inhalation have been reported since the initial use of compounds for either military devices or nuclear fuels (Carbaugh and La Bone, 2003;Okladnikova et al, 2005;Grappin et al, 2007). Similarly, accidental entry of actinides following wounding has also been reported (Ilyin, 2001;Falk et al, 2006;James et al, 2007;Sugarman et al, 2018;Klumpp et al, 2020). Indeed, case reports of incidents/accidents, biological assay data and tissues have been collated by registries in several countries (Loffredo et al, 2017;Kathren and Tolmachev, 2019) that provide a valuable source of information.…”
Section: Introductionmentioning
confidence: 99%
“…However, there are no formal protocols or recommendations for managing the emotional needs in this circumstance. In some cases, treatment decisions regarding chelation and excision may be affected by a patient's mental state (e.g., a patient who wants treatment in order to gain a feeling of control over the situation) and vice versa (e.g., a patient feeling less anxious because treatment appears to be effective) (Klumpp et al 2018(Klumpp et al , 2020. A literature review reveals that there have been no published peer-reviewed studies on the mental health of workers who have had plutonium intakes.…”
Section: Introductionmentioning
confidence: 99%
“…There are also anecdotal reports suggesting that some psychological adverse effects, which persist many months or years after treatment, may have been associated with chelation therapy. 2 Finally, a recent case study of a contaminated wound reported alarming adverse psychological events that medical providers attributed to chelation with DTPA (Klumpp et al 2020).…”
Section: Introductionmentioning
confidence: 99%